2019
DOI: 10.1002/lary.28292
|View full text |Cite
|
Sign up to set email alerts
|

Otoscopic diagnosis using computer vision: An automated machine learning approach

Abstract: Objective: Access to otolaryngology is limited by lengthy wait lists and lack of specialists, especially in rural and remote areas. The objective of this study was to use an automated machine learning approach to build a computer vision algorithm for otoscopic diagnosis capable of greater accuracy than trained physicians. This algorithm could be used by primary care providers to facilitate timely referral, triage, and effective treatment.Methods: Otoscopic images were obtained from Google Images (Google Inc., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 13 publications
(16 reference statements)
1
71
0
1
Order By: Relevance
“…Other research groups have already reported on medical image classification or otoscopic diagnosis performed using an automated deep learning approach with no coding 15 , 19 . We consider that an AI-based algorithm would also be suitable for quantification such as that in Gleason grading for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other research groups have already reported on medical image classification or otoscopic diagnosis performed using an automated deep learning approach with no coding 15 , 19 . We consider that an AI-based algorithm would also be suitable for quantification such as that in Gleason grading for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This method can automatically learn complex tasks in different fields. With 1,366 unique otoscopic images of 14 diagnoses collected from Google, Livingstone and Chau 22 have obtained sensitivities (recall) of 75% and 90.9% in the classification of AOM and OME. Our study has gained a total of 10,703 otoendoscopic images in train set and achieved sensitivities of 98.38% and 97.59% in the classification of AOM and OME in test set with Xception (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…One of the important challenges of AI in otolaryngology is high‐quality and large quantities of patient data collection 13 . Based on a large amount of otoendoscopic images, several studies have developed the feature‐extractions‐based algorithms for automatic diagnosis of OM 15–18 . Recently, deep learning methods, which reduce the need for manual feature extraction are used to automated diagnosis of ear diseases 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have applied machine learning to visible light otoscopy for identification chronic otitis media with perforation, cerumen, myringosclerosis, and retraction pockets 45 , 62 64 . Livingstone and colleagues uploaded visible light otoscopy images into a Google Cloud automated algorithm, AutoML, and compared the diagnostic accuracy of the algorithm to physicians from a variety of specialties 44 . Serous otitis media was correctly diagnosed by the algorithm 80% of the time, compared to a rate of 44% among physicians.…”
Section: Discussionmentioning
confidence: 99%